PENDIDIKAN BERBASIS TEKNOLOGI, PERMASALAHAN DAN TANTANGANNYA - Gusmiyati, Gusmiyati; Zulfakar, Zulfakar; Hariyanto, Dedy (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Technology-based education is designed to help solve educational problems, so as to be able to provide benefits in an effort to improve the quality of learning. however, in practice this is not easy. This type of qualitative-descriptive study aims to explain the problems and challenges faced in applying technology-based learning in schools. Data collection is done by observing documents. It was concluded that educational efforts adjust to technological developments, facing various constraints and challenges. However, the government and education actors continue to try to deal with this, with the hope of increasing self-competence and the quality of Indonesian education quality.